Digitalising traditional practices for farmers to monitor and manage savings - Kyokusiima, Edinah (Technical Centre for Agricultural and Rural Cooperation, 2019)
Edinah Kyokusiima, Business Analyst at Akaboxi Ltd, explains how digitalising traditional practices that farmers use to monitor and manage savings can help them document and track their transactions, thus making it easier for them to access finance from banks and other institutions.